Prikaz knjige: Stephen M. Levin: The Contemporary Anglophone Travel Novel: The Aesthetics of Self-Fashioning in the Era of Globalization - Grgurinović, Ivona (2010)
U radu se prikazuje knjiga The Contemporary Anglophone Travel Novel: The Aesthetics of Self-Fashioning in the Era of Globalization, autor Stephen M. Levin, Routledge, 2008
Projekt MZOS
HRV